Separation of similar yeast strains by IEF techniques - Horká, Marie; Růzicka, Filip; Holá, Veronika; Slais, Karel (Electrophoresis, 2009)
Rapid and reliable identification of the etiological agents of infectious diseases, especially species that are hardly distinguishable by routinely used laboratory methods, e.g. Candida albicans from C. dubliniensis, is necessary for early administration of an appropriate therapy. Similarly, the differentiation between biofilm-positive and biofilm-negative yeast strains is necessary for the choice of a therapeutic strategy due to higher resistance of the biofilm-positive strains to antifungals. In this study rapid separation and identification of similar strains of Candida, cells and/or their lysates, based on IEF are outlined. The isoelectric points of the monitored "similar pairs" of Candidas, C. albicans and C. dubliniensis and the biofilm-positive C. parapsilosis, C. tropicalis and their biofilm-negative strains were determined by CIEF with UV detection in the acidic pH gradient. The differences between their isoelectric points were up to 0.3 units of pI. Simultaneously, a fast and a simple technique was developed for the lysis of the outer membrane cell and characteristic fingerprints were found in lysate electrophoreograms and in gels from the capillary or the gel IEF, respectively.
Keywords: Sensitivity and Specificity; senzitivita a specificita; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; biofilmy; isoelektrická fokusace; Isoelectric Focusing; Biofilms; Candida